Who moved my old cheese? Implications of COVID 19 to teaching and learning in Southern Africa - Selloane Pitikoe; Karen Ferreira-Meyers; Sithulisiwe Bhebhe; Sithulisiwe Bhebhe; Nompumelelo Dlamini-Zwane (Journal of Teaching and Learning with Technology, 2021)
This reflective essay seeks to share the authors’ thoughts and feelings on the impact of COVID 19 on the general teaching and learning strategies, theories and practices in the small kingdom of Eswatini in Southern Africa. Coming from varying backgrounds in education allows the authors to tackle the overview of consequences from different points of view and angles. The common thread among the authors is an observation that the disruptive nature of the pandemic, with its sudden onslaught and the need to react fast, might lead to long-lasting transformations in the area of teaching and learning.  Emphasis in this essay is on whether online teaching and learning happened previous to the start of the pandemic and to determine its effectiveness in terms of access and self-directedness of the learners. Given the devastating impacts of COVID 19 governments had to develop ‘instant’ provisions such as digital/e-learning platforms in the formal education sector in a bid to minimize new infections through social distancing while also supporting learning outside the classroom. The question that remains unanswered though is the appropriateness and effectiveness of the digital platforms in the context of a developing country with existing socio-economic and infrastructural underlying problems; hence the rationale for this paper. In conclusion a few recommendations will be proposed in view of improving the immediate, short-term teaching and learning strategies which can later be reflected upon once the pandemic subsides.